THE EFFECT OF USING SMALL GROUP DISCUSSION METHOD ON STUDENTS’ ABILITY IN READING COMPREHENSION FOR THE ELEVENTH GRADE STUDENTS OF SMA TAMANSISWA BINJAI - efrini panjaitan; Dewi Rulia Br Sitepu; Regina Tamariahna Br Ginting (Jurnal Serunai Bahasa Inggris, 2022)
The objective of this study is to find out The Effect of Small Group Discussion Method on Students’ Ability in Reading Comprehension for the Eleventh Grade Students of SMA Tamansiswa Binjai. This study is Quasi experimental research. This study used a system of controlled class and experimental class, which acts as a controlled class benchmark basic ability student on reading comprehension without application of the method, while the experimental class was given Small Group Discussion Method. After knowing the mean obtained by the respondents in the controlled class of 49,71, it can be concluded that students' reading comprehension achievement is still low. In this study, students in the experimental class received treatment with the application of Small Group Discussion Method and it has been known that the mean data in the experimental class is 85.35, it can be concluded that students' reading cohesion achievement in the experimental class is good. Based on the calculation of validity test, it can conclude that the data has valid. Then based on the calculation of reliability of test, found that the data has reliable. After testing the homogeneity criteria of the data obtained in the controlled class and the experimental class, it has been found that the data obtained are homogeneous. After testing the data hypothesis criteria that have been obtained in the controlled class and experimental class, it has been found that the hypothesis is received, where tcount > ttable = 19.07 > 1.668, so it can be concluded that Small Group Discussion effects on Students’ Reading Comprehension Achievement of the Eleventh Grade Students of SMA Tamansiswa Binjai.